Ионный состав поровой воды мелководных шельфовых отложений моря Лаптевых; Доклады Академии наук; Т. 467, № 3 - Ульянцев А. С. Александр Сергеевич; Полякова Н. В. Наталья Владимировна; Романкевич Е. А. Евгений Александрович; Семилетов И. П. Игорь Петрович; Сергиенко В. И. Валентин Иванович (2016, 2016)
Заглавие с экрана